2020
DOI: 10.3389/fgene.2020.543294
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Population Genetic Analysis of Commercial, Indigenous, Game, and Wild Chickens Using 600K SNP Microarray Data

Abstract: Zhang et al. Genetic Structure Analysis of Populations the highest female-to-male ratios. Interestingly, RJF comprised a greater proportion of males than females. Our results show the population genetics of chickens under selection pressures, and can aid in the development of better conservation strategies for different chicken breeds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 66 publications
7
29
3
Order By: Relevance
“…It is even higher than a previous study conducted on 14 French breeds in which they observed an overall Fst of 0.19 (Berthouly et al, 2008). However the observed genetic differentiation between French breeds is larger than the one observed in Chinese populations with overall Fst of 0.11 (Qu et al, 2006) and pairwise Fst ranging from 0.03 to 0.27 (Zhang et al, 2020) while we observed values from 0.13 to 0.43 for French local breeds. This indicates that management of French local breeds succeeded in conserving a large number of distinct breeds.…”
Section: Overall Breed Structurecontrasting
confidence: 94%
See 1 more Smart Citation
“…It is even higher than a previous study conducted on 14 French breeds in which they observed an overall Fst of 0.19 (Berthouly et al, 2008). However the observed genetic differentiation between French breeds is larger than the one observed in Chinese populations with overall Fst of 0.11 (Qu et al, 2006) and pairwise Fst ranging from 0.03 to 0.27 (Zhang et al, 2020) while we observed values from 0.13 to 0.43 for French local breeds. This indicates that management of French local breeds succeeded in conserving a large number of distinct breeds.…”
Section: Overall Breed Structurecontrasting
confidence: 94%
“…These values are larger than those observed in other European breeds with an observed heterozygosity 0.19 in breeds sampled in Germany (Malomane et al, 2019) and observed heterozygosity ranging from 0.16 to 0.29 in Dutch breeds (Bortoluzzi et al, 2018) . Reversely this level of within population diversity is very close to the one observed in Asian populations with values ranging from 0.29 to 0.36 (Zhang et al, 2020) . Interestingly this corresponds to the level of diversity observed in populations less structured like the Chinese ones in which gene flow occurs regularly between breeds ensuring the conservation of a high level of within-breed genetic diversity.…”
Section: Overall Diversitysupporting
confidence: 78%
“…However, considering the costs involved and assess to technology, barcoding markers were used in the present study. SNPs have been used for genomewide analysis to assess the conservation status and the genomic variability of Italian chicken breeds [22] as well as to understand genetic structures of these (indigenous, commercial, gamecock, and wild ancestral chicken) breeds under different selection pressure [23]. Furthermore, mitogenome sequences have been utilized to assess hereditary divergence between 22 Asian native breeds and seven native Indian chicken breeds [24], to investigate phylogenetic evolution and genetic diversity of Tibetan chicken [25], Tosa-Jidori of Japan [26], Huainan Partridge [27], and Huangshan Black [28] chickens of China.…”
Section: Discussionmentioning
confidence: 99%
“…ROH islands are widely observed in populations and can be used as a useful tool to identify the phenomenon called “selective sweeps”, genome regions undergone selection pressure ( Szmatoła et al 2019 ). ROH islands have been used to localize selection signatures in the genome of farm animals including sheep ( Purfield et al 2017 ; Mastrangelo et al 2017 ; Mastrangelo et al 2018 ; Luigi-Sierra et al 2019 ; Signer-Hasler et al 2019 ), goat ( Bertolini et al 2018 ; Onzima et al 2018 ), horse ( Metzger et al 2015 ; Grilz-Seger et al 2018 ; Ablondi et al 2019 ; Grilz-Seger et al 2019 ), cattle ( Goszczynski et al 2018 ; Peripolli et al 2018 ; Nandolo et al 2018 ; Szmatoła et al 2019 ; Peripolli et al 2020 ), pig ( Wang et al 2019 ; Xu et al 2019 ; Xie et al 2019 ; Gorssen et al 2020 ) and in chicken ( Marchesi et al 2018 ; Almeida et al 2019 ; Strillacci et al 2018 ; Zhang et al 2018 ; Zhang et al 2020 ).…”
mentioning
confidence: 99%